2020
DOI: 10.1177/2372732219897093
|View full text |Cite
|
Sign up to set email alerts
|

School Pathways to the Juvenile Justice System

Abstract: School policies have increasingly criminalized students for common developmentally appropriate behaviors, such as talking back, public displays of affection, or repeated tardiness. Although their behaviors are no more problematic than their peers, children of color and children of color with disabilities are punished at higher rates. The increasing number of police in schools has also increased the number of arrests. In some cities, schools are the primary referral source to juvenile court. The literature on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Also consistent with the extant literature (Desai et al, 2012; Leiber et al, 2011; Piquero, 2008), Latinx, Black non-Latinx, and multiracial participants were significantly more likely to recidivate compared to White non-Latinx participants, after controlling for other demographics, historical legal risk factors, and two dynamic criminogenic needs (i.e., alcohol-related consequences and peer deviancy). This finding is likely reflective of racial bias documented in studies of school disciplinary practices (Okonofua & Eberhardt, 2015) and referrals to juvenile court (Hughes et al, 2020); police perceptions of criminality (Eberhardt et al, 2004); juvenile court staff diversion decisions (Love & Morris, 2019); prosecutorial discretion (Smith & Levinson, 2012); juvenile court judges’ disposition decisions (Peck & Jennings, 2016), including sentences of life without parole (Sterling, 2013); and racist media descriptions of adult Black defendants increasing the likelihood of execution (Goff et al, 2008). Thus, there is ample evidence that racial bias permeates most, if not all, aspects of the justice system and accounts for a large portion of the variance in continued involvement in the juvenile justice system as well as at initial court contact for youth, per our study, regardless of their individual-level risk.…”
Section: Discussionmentioning
confidence: 85%
“…Also consistent with the extant literature (Desai et al, 2012; Leiber et al, 2011; Piquero, 2008), Latinx, Black non-Latinx, and multiracial participants were significantly more likely to recidivate compared to White non-Latinx participants, after controlling for other demographics, historical legal risk factors, and two dynamic criminogenic needs (i.e., alcohol-related consequences and peer deviancy). This finding is likely reflective of racial bias documented in studies of school disciplinary practices (Okonofua & Eberhardt, 2015) and referrals to juvenile court (Hughes et al, 2020); police perceptions of criminality (Eberhardt et al, 2004); juvenile court staff diversion decisions (Love & Morris, 2019); prosecutorial discretion (Smith & Levinson, 2012); juvenile court judges’ disposition decisions (Peck & Jennings, 2016), including sentences of life without parole (Sterling, 2013); and racist media descriptions of adult Black defendants increasing the likelihood of execution (Goff et al, 2008). Thus, there is ample evidence that racial bias permeates most, if not all, aspects of the justice system and accounts for a large portion of the variance in continued involvement in the juvenile justice system as well as at initial court contact for youth, per our study, regardless of their individual-level risk.…”
Section: Discussionmentioning
confidence: 85%
“…Mounting evidence suggests that suspension and expulsion from school actually places children on a trajectory to do worse in school, have worse relationships with their teachers, get punished more frequently, and be at higher risk of dropping out (Noltemeyer et al, 2015). In addition, children who are suspended and expelled from school are actually more likely to end up incarcerated-a snowball of consequences and experiences linked to school exclusion that has been called the school to prison pipeline, or in this case the preschool to prison pipeline (Hughes et al, 2020). In fact, a recent study suggested that racial inequalities in arrest rates would decrease by as much as 16% if we were able to equalize the risk of school-based punishment between Black and White school children (Barnes & Motz, 2018), demonstrating the need to identify predictors of expulsion that can be targeted to reduce overall and disparate rates of early exclusionary discipline.…”
Section: Preschool Expulsionmentioning
confidence: 99%
“…These decision points may be reflected in individual teacher biases as well as policies that replicate disparities, for example zero tolerance discipline policies, and likely also are reflected in system-level policies that drive school resources as well. Practices and policies to address these disparate rates, and the influence of victimization, should include school-based interventions that address teacher-student relationships, school services/resources, as well as policies that hold schools accountable for inequities in school discipline rates (see Hughes et al, 2020). All of these practices and policies should be examined in the context of addressing the interaction between victimization, racial bias, and school discipline.…”
Section: Racial Biasmentioning
confidence: 99%